Milestones in the development of agronomic management practices in crop production - Jolánkai, Márton; Dekemati, Igor; Kassai, Mária Katalin (Acta Agraria Debreceniensis, 2018)
From the dawn of the history of the human race, agriculture has always been a profound activity of mankind producing food and feed as well as various plant originated materials for further processing. Agronomy, like any other human activity, depends on the perpetual development of knowledge and technical skills, - in a modern context – science and innovation. This paper is intended to provide the reader with information regarding the main phases of the development of agricultural production from the Neolithic societies through the early Mesopotamian and Egyptian empires to the inventions of first organised learned society of Rome. The major research findings of the past two millennia including agro-chemistry, genetics and technical development are presented. Such a review should not lead to any scientific conclusions, but rather a philosophical postulate similar to that of Jonathan Swift written some centuries ago: “And he gave it for his opinion, that whoever could make two ears of corn, or two blades of grass, to grow upon a spot of ground, where only one grew before, would deserve better of mankind, and do more essential service to his country, than the whole race of politicians put together”.